2017
DOI: 10.1007/s11604-017-0637-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the four-field box and field-in-field techniques for conformal radiotherapy of the esophagus using dose–volume histograms and normal tissue complication probabilities

Abstract: The FIF showed evident advantages over 4FB: a more homogeneous dose distribution, lower D values, and fewer required MUs, while it also retained PTV dose conformality. FIF should be considered as a simple technique to use clinically in cases with esophageal malignancies, especially in clinics with no IMRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 32 publications
4
25
2
Order By: Relevance
“…The TCP and NTCP were finally obtained based on the EUD. The parameters and endpoints for TCP and NTCP calculations were taken from previous studies (17, 29, 30) and were shown in Table 2A. More importantly, it was well-known that the parameters of the radiobiological models would influence the results, therefore, we also used the Webb-Nahum model (WN model) and the Lyman-Kutcher-Burman (LKB) model to further confirm our results of TCP and NTCP calculations.…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…The TCP and NTCP were finally obtained based on the EUD. The parameters and endpoints for TCP and NTCP calculations were taken from previous studies (17, 29, 30) and were shown in Table 2A. More importantly, it was well-known that the parameters of the radiobiological models would influence the results, therefore, we also used the Webb-Nahum model (WN model) and the Lyman-Kutcher-Burman (LKB) model to further confirm our results of TCP and NTCP calculations.…”
Section: Methodssupporting
confidence: 57%
“…Additionally, these studies have mainly focused on analysis of dose volume histogram (DVH) and dose distributions to evaluate RT plans. However, in some cases in which the treatment plans yield similar levels of dosimetric performance, analyzing other indices based on radiobiology may be essential when attempting to precisely evaluate the treatment outcome, particularly in terms of tumor control and normal tissue sparing (16, 17). But this issue is not received enough attention and the relevant data is rare.…”
Section: Introductionmentioning
confidence: 99%
“…Using consensus target contours, Allaveisi (2017) compared the four-field box and field-in-field techniques in terms of conformity, homogeneity, mean dose, and maximum dose [ 16 ]. The field-in-field technique resulted in a more homogenous dose distribution with a similar conformality.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Yavas et al 21 reported that the FIF technique, compared to the 3D-CRT for the whole breast radiotherapy caused a significant decrease in the maximum dose and mean dose of the PTV. In their study, Allaveisi et al 24 compared the 4-field conformal radiotherapy and FIF radiotherapy of the esophagus and found that FIF causes reduction in the maximum dose of PTV. Therefore, in terms of these parameters, the result of the present study is in agreement with those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…, Yavas et al 26 , Ercan et al 12 , and Allaveisi et al 24 who compared the two techniques and showed significant improvement in HI with the FIF technique. However in the field of CI, there was no significant difference between the two techniques, which was in agreement with the previous study by Baycan et al 13 In terms of total MU, the present study did not show any significant difference between the two techniques, which was in agreement with the previous study by Chui et al 27 In their study, Allaveisi et al 24 found a significant difference between both techniques, because in other studies wedge-based radiation fields are used in the 3D-CRT technique, 21,28 which can be explained by the fact that MU doses are higher with wedge-based plans because of radiation scatter.…”
mentioning
confidence: 99%